Election Campaign through Social Media: The Political impact of Facebook, Instagram, Twitter and Youtube on Voting Decision in Lanao Del Sur, Philippines - Jawad Z. Salic (Jurnal Multidisiplin Madani, 2023)
In view of social media, it now turned as the primary source of information, e.g., Facebook, Instagram, Twitter, and YouTube. Every politician wants to have a strong influence on the public. The majority sorted out that social media had turned out to be an approach to finding out about selecting an aspirant for a government position. On the other hand, political candidates nowadays add social media campaigns as one of their political campaign strategies. This study examines how social media has an emotional impact on the decisions of selected voters in the province of Lanao del Sur after surfing a social media to promote economic agenda in a political campaigns. This investigation shows that social media political information does affect the voting conclusions of the selected respondents